3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/08 04:30:42
3(2X+1)=X(X+1)用因式分解法解方程.必须用因式分解法.3(2X+1)=X(X+1)用因式分解法解方程.必须用因式分解法.3(2X+1)=X(X+1)用因式分解法解方程.必须用因式分解法.3
3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.
3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.
3(2X+1)=X(X+1) 用因式分解法解方程.
必须用因式分解法.
3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.3(2X+1)=X(X+1) 用因式分解法解方程.必须用因式分解法.
原方程就是X^2-5x-3=0
X^2-5x+25/4-37/4=0
(x-5/2)^2-(√37/2)^2=0
(x-5/2+√37/2)(x-5/2-√37/2)=0
x=5/2-√37/2或者x=5/2+√37/2
(x^3-x^2)+(x-1)因式分解
3x(2X+1)=4x+2因式分解
因式分解:(3x-2)(x+1)=4-6x
x(x-1)-3x+4=(x-2)^2因式分解用因式分解的方法解上面的方程
因式分解 (x+1)(x-3)
x^2+x+1因式分解
因式分解:(x+1)(x+2)(x+3)(x+4)+1
x^2+1=x(x+1/x)是不是因式分解
因式分解:x^4+x^3-2x^2-x+1
(x-1)(x-2)(x-3)(x-4)-24 因式分解
(x+1)(x+2)(x+3)(x+4)-24因式分解
x^4+x^3-4x^2+x+1因式分解
因式分解(x+1)(x+2)(x+3)(x+4)-24
因式分解(x-1)(x+2)(x+3)(x+6)-13
因式分解(X+1)(X+2)(X+3)(X+4)-120
因式分解(x+1)(x-2)(x-3)(x-6)+20
因式分解(x+1)(x+2)(x+3)(x+4)-120
因式分解1+x+x^2+x^3+```+x^15